Stability of yield and related traits in dual-purpose sorghum (Sorghum bicolor) across locations - V, A; BHAT, B VENKATESH; HARIPRASANNA, K; RAMANA, O V (The Indian Journal of Agricultural Sciences, 2012)
The present study detected differential response in 10 dual-purpose sorghum genotypes over locations for fodder and biomass yields, which are very important agronomic traits. The G × E (linear) as well as pooled deviation mean squares were found significant for these traits indicating that the linear sensitivity of different genotypes is variable and performance of genotypes fluctuated significantly from their respective linear path of response to environments. The test hybrid ‘SPH 1467’ had the highest phenotypic index and was found stable for fodder and biomass yields. Among the varieties, ‘SPV 1750’ recorded the highest grain yield while ‘SPV 1716’ had the highest fodder and biomass yield, but were not stable across locations for these traits. The genotype ‘SPV 1616’ showed high adaptability for grain and fodder yields and biomass, and hence better suited as a dual purpose sorghum variety.